Optical circular polarization of blazar S4 0954+65 during high linear polarized states: letters to the editor - Liodakis, Ioannis; Shablovinskaya, E.; Blinov, D.; Savchenko, S. S.; Malygin, E.; Kotov, S.; Kiehlmann, S.; Readhead, A. C. S.; Potter, S. B.; Rieger, Frank M.; Grishina, T. S.; Hagen-Thorn, V. A.; et al. (Astronomy and astrophysics, 2023)
Optical circular polarization observations can directly test the particle composition in black hole jets. We report the first observations of the BL Lac-type object S4 0954+65 in high linear polarized states. While no circular polarization was detected, we were able to place upper limits of < 0.5% at 99.7% confidence. Using a simple model and our novel optical circular polarization observations, we can constrain the allowed parameter space for the magnetic field strength and composition of the emitting particles. Our results favor models that require magnetic field strengths of only a few Gauss and models in which the jet composition is dominated by electron-positron pairs. We discuss our findings in the context of typical magnetic field strength requirements for blazar emission models.
Gesehen am 20.08.2024